Transjugular Intrahepatic Portosystemic Shunt (TIPS): Pathophysiologic Basics, Actual Indications and Results with Review of the Literature - Strunk, Holger; Marinova, Milka (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Background Transjugular intrahepatic portosystemic shunt (TIPS) is a non-selective portosystemic shunt created using endovascular techniques. During recent years technical improvements and new insights into pathophysiology have modified indications for TIPS placement. In this article we therefore want to discuss current knowledge.Method A literature review was performed to review and discuss the pathophysiology, indications and results of the TIPS procedure.Results Established TIPS indications are persistent bleeding despite combined pharmacological and endoscopic therapy and rebleeding during the first five days. A new indication in the European recommendations is early TIPS placement within 72 hours, ideally within 24 hours, in patients bleeding from esophageal or gastroesophageal varices at high risk for treatment failure (e. g. Child-Pugh class C < 14 points or Child-Pugh class B with active bleeding) after initial pharmacological and endoscopic therapy. For prevention of recurrent variceal hemorrhage in the recommendations, covered TIPS placement is the treatment of choice only after failed first-line therapy, although numerous TIPS studies show a prolonged time to rebleeding and a reduction of mortality. Similarly for secondary prophylaxis in patients with refractory ascites, covered TIPS placement may be considered only if the patient continues to be intolerant to NSBBs and is an appropriate TIPS candidate even though studies show that the TIPS procedure controls ascites, improves survival and renal function better than paracentesis. Potential indications for TIPS implantation are Budd-Chiari syndrome, acute portal vein thromboses, hydrothorax, hepatopulmonary and hepatorenal syndrome (Typ 2), portal hypertensive gastropathy (PHG) and prophylaxis of complications of abdominal surgery, very rarely bleeding in ectopic varices or in patients with chylothorax or chylous ascites.Conclusion TIPS placement is an established procedure with a new indication as “early TIPS”. In the European recommendations it is only the second-line therapy for prevention of recurrent variceal hemorrhage and for secondary prophylaxis in patients with refractory ascites although several studies showed a clear benefit of the TIPS procedure compared to ligation and NSBBs.Key Points Citation FormatHintergrund Der transjuguläre intrahepatische portosystemische Shunt (TIPS) ist eine nicht operative Intervention zur Druckentlastung des Pfortadersystems. Technische Entwicklungen der letzten Jahre und erweiterte zugrundeliegende pathophysiologische Kenntnisse haben die Indikationen zur TIPS-Platzierung geändert. Im vorliegenden Review soll daher auf den gegenwertigen Kenntnisstand eingegangen werden.Methode Dazu werden anhand der Literatur gegenwärtige Indikationen im Hinblick auf pathophysiologische Grundlagen, Indikationen und Ergebnisse aufgezeigt und diskutiert.Ergebnisse Etablierte Indikationen für einen TIPS waren und sind die akute, endoskopisch nicht kontrollierbare Varizenblutung und die Re-Blutung innerhalb von 5 Tagen. Neu in die europäischen Empfehlungen aufgenommen wurde der Einsatz des TIPS in der Behandlung der akuten Ösophagus- und gastroösophagealen Varizenblutung als sogenannter „early TIPS“. Zur sekundären Blutungsprävention wird ein TIPS erst nach Versagen der Erstlinientherapie angegeben. Neuere Studien zeigen jedoch, dass durch die TIPS-Implantation eine Verlängerung des blutungsfreien Intervalls sowie Reduzierung der Mortalität möglich ist. Bei therapie-refraktärem Aszites wird ein TIPS nur bei den Patienten empfohlen, die nicht auf die Behandlung mit NSBB ansprechen, obwohl Studien gezeigt haben, dass durch den TIPS, verglichen mit der Paracentese, die glomeruläre Filtrationsrate steigt, der Aszites besser kontrolliert und das Überleben verbessert werden kann. Weitere mögliche Indikationen sind der Einsatz des TIPS beim Budd-Chiari-Syndrom, bei der akuten Pfortaderthrombose, beim Hydrothorax, dem hepatopulmonalen und hepatorenalen Syndrom (Typ 2), bei Patienten mit einer transfusionspflichtigen portalen hypertensiven Gastropathie sowie zur Prophylaxe von Komplikationen vor geplanten abdominellen operativen Eingriffen, selten bei Blutungen durch ektope Varizen oder bei Chylothorax bzw. chylösen Aszites.Schlussfolgerung Der TIPS ist ein mittlerweile etabliertes Verfahren mit einer neuen Indikation als „early-TIPS“. Obwohl der bisherigen Therapie durch Ligation und Betablockern klar überlegen, steht er in den europäischen Empfehlungen bei der sekundären Prävention einer Blutung nur an zweiter Stelle, ebenso wie beim therapie-refraktären Aszites.Kernaussagen Zitierweise
Keywords: TIPS; porto-systemic shunt; stent-grafts; esophageal varices; transhepatic; ascites